(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In this article I analyze Wojciech Kudyba’s novel “My name is Maidan» (“Nazywam się majdan»), which is an attempt to tell a fictionalized story of the Ukrainian renaissance of the recent years. I investigate the symbols, the rhetorical terms, and the literary conventions that the author evokes. In his novel Kudyba poses the questions about the specificity and the roots Ukrainian national identity and its relations with the culture of Western Europe.